Equity Valuation : LinkedIn Corp - Silva, José Miguel de Figueiredo Bettencourt Moreira da (2016)
The aim of this dissertation was to reach Linkedln's Equity Fair Value. Through an analysis of all methods available, the ones chosen were Adjusted Present Value and Relative Valuation through a combination of Equity Multiples, Transaction Multiples, Trading Multiples and Social Network Specific Multiples (Monthly Active Users). Adjusted Present Value valuation yielded a per share value for Linkedln of $ 186,77. As for Relative Valuation, Equity Multiplies showed an average price target of $ 143, Transaction Multiples gave a $ 87,57 valuation, Trading Multiples averaged $ 216,14 and Monthly Active Users a quite distant $ 6,35. ln order to achieve more robustness in this forecast, sensitivity analysis were run, including multiple scenario analysis, to test different revenue projections, and variations on specific variables. Finally, a comparison was run against J. P. Morgan's report to measure up this dissertation's conclusions to an actual investment bank analysis. This dissertations final conclusion was to propose a Sell recommendation on Linkedln who presented a closing price on December 1st 2015 of $ 249,82. Which is in contrast with J. P. Morgan's Buy recommendation of $ 300 price target.